THE IMPACT OF COMPENSATION, WORK MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT X - Dinda Rizka Aulia; Nugraha Saefuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Employee performance at PT X has faced significant challenges, evidenced by a decline in Key Performance Indicator (KPI) achievements from 82% in 2023 to 74% in 2025, consistently falling below the organizational target of 85%. This decline is purportedly linked to compensation levels that remain below industry standards and low employee satisfaction regarding career development and recognition. This study analyzes the impact of compensation, work motivation, and job satisfaction on employee performance at PT X. A quantitative research design employing multiple linear regression analysis was applied. The study population consisted of all permanent employees of PT X, totaling 33 respondents, selected using a census sampling technique. Data were processed using SPSS version 27. The results reveal that compensation exerts a statistically significant positive impact on employee performance (p = 0.036). Work motivation does not show a statistically significant impact (p = 0.068). In contrast, job satisfaction demonstrates a strong and significant positive impact on employee performance (p < 0.001). Simultaneously, compensation, work motivation, and job satisfaction significantly influence employee performance (F = 899.866; p < 0.001). The Adjusted R² value of 0.988 indicates that 98.8% of the variance in employee performance is explained by the research model.